Genetics-based methods for agricultural insect pest management - Alphey, N; Bonsall, M (Wiley, 2017)
1. The sterile insect technique is an area-wide pest control method that reduces agricultural pest populations by releasing mass-reared sterile insects that compete for mates with wild insects. Contemporary genetics-based technologies have been developed that use insects that are homozygous for a repressible dominant lethal genetic construct rather than being sterilized by irradiation. 2. Engineered strains of agricultural pest species, including moths such as the diamondback moth Plutella xylostella and fruit flies such as the Mediterranean fruit fly Ceratitis capitata, have been developed with lethality that only operates on females. 3. Transgenic crops expressing insecticidal toxins are widely used; the economic benefits of these crops would be lost if toxin resistance spread through the pest population. The primary resistance management method is a high-dose/refuge strategy, requiring toxin-free crops as refuges near the insecticidal crops, and toxin doses sufficiently high to kill wild-type insects and insects heterozygous for a resistance allele. 4. Mass-release of toxin-sensitive engineered males (carrying female-lethal genes), as well as suppressing populations, could substantially delay or reverse the spread of resistance. These transgenic insect technologies could form an effective resistance management strategy. 5. We outline some policy considerations for taking genetic insect control systems through to field implementation.